Volunteering for Linked Data Wrapper maintenance: A platform perspective. (March 2020) - Azpeitia, Iker; Iturrioz, Jon; Díaz, Oscar
Abstract: Linked Data Wrappers (LDWs) turn Web APIs into RDF end-points, leveraging the Linked Open Data cloud with current data. Unfortunately, LDWs are fragile upon upgrades on the underlying APIs, compromising LDW stability. Hence, for API-based LDWs to become a sustainable foundation for the Web of Data, we should recognize LDW maintenance as a continuous effort that outlives their breakout projects. This is not new in Software Engineering. Other projects in the past faced similar issues. The strategy: becoming open source and turning towards dedicated platforms. By making LDWs open, we permit others not only to inspect (hence, increasing trust and consumption), but also to maintain (to cope with API upgrades) and reuse (to adapt for their own purposes). Promoting consumption, adaptation and reuse might all help to increase the user base, and in so doing, might provide the critical mass of volunteers, current LDW projects lack. Drawing upon the Helping Theory, we investigate three enablers of volunteering applied to LDW maintenance: impetus to respond, positive evaluation of contributing and increasing awareness. Insights are fleshed out through SYQL, a LDW platform on top of Yahoo's YQL. Specifically, SYQL capitalizes on the YQL community (i.e. impetus to respond), provides annotation overlays to easy participation (i.e. positive evaluation of contributing), and introduces a Health Checker (i.e. increasing awareness). Evaluation is conducted for 12 subjects involved in maintaining someone else's LDWs. Results indicate that both the Health Checker and the annotation overlays provide utility as enablers of awareness and contribution. Highlights: The problem of Linked Data Wrappers (LDW) is analyzed. A platform for LDW maintenance tapping into Yahoo's YQL has been developed. W3C's Best Practices and the Helping Theory guide the platform design. The notions of "health checker" and "re-engineering" are introduced.